Posisi Madrasah dan Pesantren dalam Politik Pendidikan di Indonesia - Suhendra, Ade (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2020)
This paper describe about how the position of madrasa and Islamic Boarding Shool on political education in Indonesia, from the development of the position of madrasa and Islamic Boarding School on Netherlands Colonial time, new order time (the start of Indonesia independence) till now. The role of madrassas and pesantren since the pre-independence era or the Dutch colonial era, the early period of independence (the Old Order), the New Order until now continues to experience significant development that is starting from the madrasa and boarding schools have not been included as part of the National Education System, until now it has become part from the National Education System.